APPLICATION OF SCRAMBLE MODEL IN IMPROVING BEGINNING READING ABILITY OF GRADE 1 STUDENTS OF ELEMENTARY SCHOOL JEUMPET ACEH BESAR - Huddin, Musfia; Safiah, Intan; Hasniyati, Hasniyati (Universitas Syiah Kuala, 2025)
Reading is an important key in the learning process, lack of reading ability is a problem in this study. Students still stutter when reading, when students are asked to read some simple sentences presented by the teacher in front of the class, students need quite a long time to read and are not fluent. The problem in this study is